Model of Employee Motivation and Cooperative Performance - Mulyani, Sitti Rizki; Sari, Vivi Nila; Sari, Marta Widian (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of this study was to determine the effect of leadership and compensation on motivation and also its implications on the performance of cooperative employees in Padang. The method used was descriptive - verifying with a survey to 330 employees. Data analysis was made using the structural equation model program (SEM) with linear structural relationship (LISREL) 8.80. The results showed that: 1) leadership and compensation have a significant positive effect on motivation. 2) Leadership, compensation and motivation have a positive and significant impact on employee performance.